2017
DOI: 10.1038/s41598-017-09281-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungal community assemblage of different soil compartments in mangrove ecosystem

Abstract: The fungal communities of different soil compartments in mangrove ecosystem are poorly studied. We sequenced the internal transcribed spacer (ITS) regions to characterize the fungal communities in Avicennia marina root-associated soils (rhizosphere and pneumatophore) and bulk soil compartments. The rhizosphere but not pneumatophore soil compartment had significantly lower fungal species richness than bulk soil. However, bulk soil fungal diversity (Shannon diversity index) was significantly higher than both pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
2
19
0
2
Order By: Relevance
“…Tremellomycetes were exclusively detected in rhizosphere soil. Other classes of Basidiomycota detected in our study are Cystobasidiomycetes and Agaricomycetes, which have also been detected in some previous studies of mangrove ecosystems [13,37].…”
Section: Ascomycota Was the Most Frequently Detected Fungal Phylumsupporting
confidence: 87%
“…Tremellomycetes were exclusively detected in rhizosphere soil. Other classes of Basidiomycota detected in our study are Cystobasidiomycetes and Agaricomycetes, which have also been detected in some previous studies of mangrove ecosystems [13,37].…”
Section: Ascomycota Was the Most Frequently Detected Fungal Phylumsupporting
confidence: 87%
“…Abou Kanani and Shengeh, unclassified sequences represented more than 80% of the good quality sequences found in the rhizosphere. The high percentage of unclassified sequences in this compartment seems to be a common finding when using the same fungal database 38 , less pronounced in annual plants though 39 . According to data here obtained, the olive rhizosphere carries a huge fungal diversity yet to be discovered.…”
Section: Discussionmentioning
confidence: 69%
“…Mangrove has been reported to be rich in biological diversity (Dias et al, 2012). Previous studies showed that some fungal species are common in the rhizosphere and different parts of the mangrove tree (Sanka Loganathachetti, Poosakkannu & Muthuraman, 2017; Prihanto, Caisariyo & Pradarameswari, 2019). The saline environment, the special life cycle of marine fungi and the unique marine fungal-host interactions make them a valuable source of secondary metabolites (Balabanova et al, 2018; Deshmukh, Prakash & Ranjan, 2018).…”
Section: Introductionmentioning
confidence: 99%